2022
DOI: 10.3233/shti220926
|View full text |Cite
|
Sign up to set email alerts
|

A Business Analytics Framework for Primary Care

Abstract: In this paper, we present a Business Analytics (BA) framework, which addresses the challenge of analysing primary care outcomes for both patients and clinicians from multiple data sources in an accurate manner. A review of the process monitoring literature has been conducted in the context of healthcare management and decision making and its findings have informed the formulation of a BA conceptual framework for process monitoring and decision support in primary care. Furthermore, a real case study is conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Similar algorithms by the research team have been used for dashboards for atrial fibrillation 43 , influenza vaccine effectiveness 26 , and virological surveillance 44 , which have been peer-reviewed. The same research team also recently reported that their respective dashboards, which are economical and easy to scale-up, had been effective in increasing flu vaccination, medicine optimisation, improving diabetes care and impact on primary care quality 45 . Thus although this piece of work is not validated for asthma yet, we have evidence from similar exercise in RSC for other disease areas that such a RSC-dashboard has led to improvement.…”
Section: Discussionmentioning
confidence: 97%
“…Similar algorithms by the research team have been used for dashboards for atrial fibrillation 43 , influenza vaccine effectiveness 26 , and virological surveillance 44 , which have been peer-reviewed. The same research team also recently reported that their respective dashboards, which are economical and easy to scale-up, had been effective in increasing flu vaccination, medicine optimisation, improving diabetes care and impact on primary care quality 45 . Thus although this piece of work is not validated for asthma yet, we have evidence from similar exercise in RSC for other disease areas that such a RSC-dashboard has led to improvement.…”
Section: Discussionmentioning
confidence: 97%